EFFECT OF PRENATAL METHYLMERCURY-INDUCED AND DHA (DOCOSAHEXAENOIC ACID) ADMINISTRATION IN AUTISM MICE MODEL - Berliani, Tiara
Correlation between mercury exposure through fish consumption with autism increased public awareness, there is emerging evidence supporting the hypothesis that autism may result from mercury prenatal exposure. Mercury exposure causes damage until death of brain neurons, which is these conditions found in autism diagnosis as well. DHA is known to enhance brain function and amelioration of behavioral symptoms exhibited by children with autism The aims of this study are to determine whether prenatal methylmercury exposure can form autism mice model and the effect of DHA on the improvement of behavior associated with autism. Autism mice model was induced by single oral dose 4 mg/Kg and 8 mg/Kg of methylmercury and given at gestation day-10 (GD10). DHA was given before (pre-treatment) and after (post-treatment) methylmercury exposure. The effect of methyl mercury and DHA was observed by behavioral test in mice offspring (F1). Behavioral test consisted observation of locomotor activity, abnormality social interactions, repetitive behavior and intelligence test. F1 mice from mother that induced by 8 mg/Kg of methylmercury: in locomotor activity test, male traveled significantly longer than controls (p<0.05); in Social Interaction Abnormaity Test, Social Preference Index of males was significantly lower than controls (p<0.05); then in repetitive behavior test, the number of marbles buried by male and female were significantly more than control (p<0.05) while time accumulative grooming and digging in males and females significantly longer than controls (p<0.05); latency in intelligence test on male significantly higher compared with controls (p<0.05). In repetitive behavior test, both DHA pretreatment and posttreatment in males and females were buried less of marbles than methylmercury group, but only significant in male (p<0.05), as well as digging activity that are significantly shorter than methylmercury group(p<0.05). In the intelligence test, latency F1 males of DHA group posttreatment is shorter than the methylmercury group (p<0.005). Oral administration of methylmercury prenatal dose 8 mg/Kg affected F1 as shown in behavioral disorders such as hyperactivity, social interaction deficits, repetitive behaviors, and also deficits of spatial memory. Effect of methylmercury on behavioral disorders different between F1 male and female. Mother that induced by methylmercury 8 mg/Kg generated behavioral disorder that commonly found in F1 male. Single oral dose 8 mg/Kg prenatal of methylmercury exposure on GD10 potentially form of autism model in mice. Suplementation of DHA prenatal that administered after exposure to methylmercury showed improvement of repetitive behavior disorders and spatial memory deficits in mice F1.